Relationship between the types of urinary incontinence, handgrip strength, and pelvic floor muscle strength in adult women - Bağ Soytaş, Rabia; Soytaş, Mustafa; Danacıoğlu, Yavuz Onur; Çitgez, Sinharib; Yavuzer, Hakan; Can, Günay; Önal, Bülent; Döventaş, Alper (Wiley, 2021)
Aim To investigate the relationship between handgrip strength with types of urinary incontinence (UI) and pelvic floor muscle strength (PFMS) in women. Methods Ninety-two women, who presented to the geriatric and urology outpatient clinics complaining of UI between July 2019 and February 2020 and had indicated to undergo urodynamic assessment after basic neurourological evaluation, were included in this cross-sectional study. The presence and types of UI were identified by clinical examination and urodynamic studies. Demographic parameters, anthropometric data, comorbidities and medications were recorded. The International Consultation on Incontinence Questionnaire-Short Form was applied. Handgrip strength (HGS) was measured by a hand dynamometer. The PFMS was subjectively assessed via vaginal digital palpation and measured quantitatively by the vaginal probe of the perineometer. Results Thirty-eight urodynamic stress, 28 detrusor overactivity, 26 urodynamic mixed UI patients were reported. Perineometer measurements were significantly lower in the urodynamic stress UI group compared to the other two groups (p = 0.020). There was no relationship between the types of urinary incontinence and HGS. However, a positive correlation was found between PFMS and HGS (p = 0.045, r = 0.298). Conclusion The positive correlation between HGS and PFMS indicates that low HGS may be a marker for PFMS weakness. Furthermore, the association between sarcopenia and UI may be explained by this condition.
Keywords: Handgrip Strength; Pelvic Floor Muscle Strength; Perineometer; Sarcopenia; Urinary Incontinence; Women